2020
DOI: 10.26803/ijlter.19.12.14
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Predictors of Academic Plagiarism among University Students

Abstract: Academic plagiarism is increasingly becoming a challenge to academic integrity worldwide, owing to the ease of access to free information online. The aim of this paper was twofold; first, to ascertain the perceptions of transport and logistics management university students regarding academic plagiarism, and second, to determine the predictors of university students’ plagiarism practices. A self-designed structured questionnaire was developed to collect information from the students of their understanding of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…I want to do the right thing," portraying a reasonable degree of integrity leadership. The case also relates well with earlier findings that plagiarism is affected by students' level of understanding (Nabee et al, 2020; and internalization (Labib et al, 2021) of plagiarism and its impact. Beyond comprehending the issue, M40+ internalized the need to abandon the misconduct for the long-term divine blessing mentioned extremely briefly by the instructor in reference to a specific section of the holy book of Islam (the Quran), while welcoming similar input from other religions.…”
Section: List Only 31%supporting
confidence: 88%
“…I want to do the right thing," portraying a reasonable degree of integrity leadership. The case also relates well with earlier findings that plagiarism is affected by students' level of understanding (Nabee et al, 2020; and internalization (Labib et al, 2021) of plagiarism and its impact. Beyond comprehending the issue, M40+ internalized the need to abandon the misconduct for the long-term divine blessing mentioned extremely briefly by the instructor in reference to a specific section of the holy book of Islam (the Quran), while welcoming similar input from other religions.…”
Section: List Only 31%supporting
confidence: 88%
“…Similarly, the findings on the perception of the dimensions of academic plagiarism can be compared with the work of Nabee et al [4], who determined the mean and standard deviation for each of the items that described the most important aspects in the perception of plagiarism by students, such as knowing the anti-plagiarism policy of the university, knowing if the application of Turnitin helps to be aware of the plagiarism, knowing if paraphrasing is plagiarism and perceiving if plagiarism in the university is normal. In this sense, the studies are similar, since they handle the possible dishonest behaviors that academic plagiarism involves.…”
Section: Discussionmentioning
confidence: 97%
“…In this sense, the studies are similar, since they handle the possible dishonest behaviors that academic plagiarism involves. However, Nabee et al [4] identified other predictive aspects of plagiarism practices and did not break academic plagiarism into dimensions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In writing an academic paper, it is easy to get a lot of resources and cheat from them without citing. Therefore, the use of a plagiarism checker is to save the copyrights from violation for the publishers, but some publishers who are using some antiplagiarism soft-wares over the internet need more effort to detect the plagiarism or cannot be detected at all (Nabee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%